2016
DOI: 10.1016/j.neuron.2016.04.045
|View full text |Cite
|
Sign up to set email alerts
|

Orbitofrontal Cortex Value Signals Depend on Fixation Location during Free Viewing

Abstract: SUMMARY In the natural world, monkeys and humans judge the economic value of numerous competing stimuli by moving their gaze from one object to another, in a rapid series of eye movements. This suggests that the primate brain processes value serially, and that value-coding neurons may be modulated by changes in gaze. To test this hypothesis, we presented monkeys with value-associated visual cues, and took the unusual step of allowing unrestricted free viewing while we recorded neurons in the orbitofrontal cort… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

21
112
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 101 publications
(133 citation statements)
references
References 56 publications
21
112
0
Order By: Relevance
“…This possibility accounts for a remarkable feature of McGinty et al (2016)'s study (Figure 1, middle panel). They found classic OFC reward-related responses in the absence of any economic choice task.…”
Section: New Data Supporting the Relationship Between Attention And Rmentioning
confidence: 69%
See 1 more Smart Citation
“…This possibility accounts for a remarkable feature of McGinty et al (2016)'s study (Figure 1, middle panel). They found classic OFC reward-related responses in the absence of any economic choice task.…”
Section: New Data Supporting the Relationship Between Attention And Rmentioning
confidence: 69%
“…Research published in this issue of Neuron from McGinty et al (2016) suggests that attention may help bind information about value to specific options in economic choice. Responses of orbitofrontal neurons are strongly modulated by the distance from gaze to the position of a reward-predicting target.…”
mentioning
confidence: 99%
“…Several recent studies have shown that value representations in the prefrontal cortex can be influenced by how attention is allocated among visual objects of different value. This includes overt shifts of attention (gaze) performed during natural free viewing (McGinty et al, 2016;Hunt et al, 2018), as well as covert shifts of attention performed in the absence of saccadic eye movements (Xie et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…A natural hypothesis emerging from these studies is that attention, by modulating neural value signals, may influence a wide range of value-driven behaviors. To test this hypothesis, we build upon our recent report of gazemodulated value signals in the primate orbitofrontal cortex during appetitive Pavlovian conditioning (McGinty et al, 2016). Whereas the prior report considered only the neural effects of gaze, here we address both the neural and behavioral effects, and ask whether the neural effects are sufficient to explain behavior.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation